EVALUATION OF PORTFOLIO PERFORMANCE AT PT SINARMAS SEKURITAS INDONESIA IN THE JANUARY-DECEMBER 2021 PERIOD BASED ON THE SHARPE, TREYNOR AND JENSEN INDEX - N. Mazaniyyah; Giyah Yuliari; Hikmah Hikmah; Sri Suyati (Universitas 17 Agustus 1945 Semarang, 2023)
Stock Prices Fluctuation affected by market conditions indicates that the company is not doing well. Fluctuations in the share price of Sinarmas Sekuritas Indonesia are influenced by unstable market conditions. The aim of this study is to find out whether the stocks which have been recommended by PT. Sinarmas Sekuritas Indonesia 2021 is superior or inferior. The data used in this study were in the form of secondary data contained in the Market Outlook published by PT. Sinarmas Sekuritas Indonesia, which consisted of 33 stocks during the research period. Moreover, this type of research used case studies. The result of the study shows that the value of the regression constant is negative with a significance value smaller than the significance level of 0.05. Thus, it can be concluded that the performance of PT Sinarmas Sekuritas Indonesia's stock portfolio for the January–December 2021 period is inferior which shows that the performance of the portfolio with the index has bad performance. In addition, companies whose shares have good performance are expected to maintain their company's performance, while companies that have bad performance can improve their company's performance.